- Tinjauan Pidana Kesusilaan Dimuka Umum Yang Dilakukan Oleh Militer (Put. No. 110-k/PMT-K/BDG/AD/XI/2019) (Studi Putusan No.26/Pid.Sus/2021/PN Kph): - - Azhari Halin Hutapea; Aprima Suar (Fakultas Hukum Universitas Trisakti, 2023)
The military personnel of the TNI are subject to the law. Regarding the exercise of judicial authority, a military court must be used for the trial. In this instance, using military justice to construct of the personnel. The military personnel of the TNI is breaking the law. Problem statement: What is the penalty for military personnel who violate public decency laws? And why did the judge impose further military criminal sanctions on personnel who commit crimes against decency in public? Analytical descriptive in character, normative legal studies is the study methodology used. The study's findings, analysis, and conclusion, which pertain to Article 281 of the prosecutor's indictment against those who committed the crime of decency In this case, the prosecution is only seeking a sentence of seven months in prison since the defendant planned to receive that sentence, and the author believes that the Auditor made mistakes during the prosecution. The maximum prison term is 2 years and 8 months due to the requirement in Article 281, Paragraph 1 of the Criminal Code, and this decision is also in conformity with the provisions in STK Panglima TNI No. 198 of 2005 connected to decency.